High‐dose chemotherapy followed by autologous stem cell rescue in Wilms tumors: French report on toxicity and efficacy. Issue 3 (22nd November 2021) - Delafoy, Manon; Verschuur, Arnauld; Scheleirmacher, Gudrun; Tabone, Marie‐Dominique; Sudour‐Bonnange, Hélène; Thébaud, Estelle; Freycon, Claire; Notz‐Carrère, Anne; Boulanger, Cécile; Pellier, Isabelle; Irtan, Sabine; Muracciole, Xavier; et al.
Abstract: Background: Heterogeneous data have been reported on high‐dose chemotherapy (HDCT) with autologous stem cell rescue (ASCR) in Wilms tumors (WTs). We aimed to define its safety and efficacy in the French cohort, and to compare this management to current international recommendations. Methods: Data prospectively collected from children, adolescents, and young adults with WT treated with HDCT/ASCR between 2000 and 2016 in French centers were retrospectively analyzed. Toxicity was reported according to CTCAE v4.03. Results: Fifty‐four patients received HDCT/ASCR (first line, n  = 13; recurrence, n  = 41). Their median age at the time of ASCR was 5.3 years (range 2.2–21.6). Main nonhematological acute grades 3–4 toxicities were digestive and renal. No significant difference of toxicity rate was observed among HDCT regimens and schedules. Two patients died shortly after ASCR (renal and multiorgan failure), and one heavily pretreated patient died of late respiratory failure. The selection criteria applied to define those patients eligible for HDCT/ASCR retrospectively matched to those currently used in the International Society of Pediatric Oncology (SIOP) UMBRELLA protocol for 38 patients, with encouraging survival rates compared to published data. The objective response rate to HDCT was 21%, with a disease control rate after HDCT of 85%. After a median follow‐up of 7 years, the 5‐year event‐free survival (EFS) and overall survival (OS) were 54% (95% CI: 32%–76%) and 62% (95% CI: 31%–82%) for frontline patients, and 57% (95% CI: 39%–71%) and 69% (95% CI: 52%–81%) at recurrence. Conclusion: HDCT was feasible and showed encouraging results in well‐defined settings. Data from the current prospective protocol will help to better evaluate HDCT impact on survival.